Impact of Corporate Social Responsibility on Economic Value Added: The Role of the Supply Chain Management Environment at LQ45 Indonesia - Hana Nabilah Rahma; Hersugondo Hersugondo (LPPM Universitas Terbuka, 2022)
Purpose – This research examined the effect and strategy of CSR (Corporate Social Responsibility) on EVA (Economic Value Added) using the SCME mechanism. Methodology – Population data sets were derived from the index LQ45 for the period of August 2022 and compared to the previous six years. Furthermore, a purposive sampling technique was applied to conduct a regression analysis, while mediation used the Hayes process version 4.2, Model 8. The data set was compiled using information from IDX, Bloomberg, and Eikon platforms (Thomson Reuters). Findings – The results highlighted four key conclusions, as follows: High CSR index companies observed a rise in EVA; SCME mediates the effects of CSR on EVA; Company size considerably modifies the effect of CSR on EVA; Company size significantly modifies the effect of CSR on SCME. Originality – This research represents a novel attempt to investigate the relationship between CSR and EVA, the company size dimension's mediative role, and the SCME mediating role in Indonesia's LQ45 Index. The results present intriguing management, policy, and literature implications.